2016
DOI: 10.1002/2016jc011714
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modulation of air‐sea CO2 flux in Drake Passage

Abstract: We investigate the role of mesoscale eddies in modulating air‐sea CO2 flux and associated biogeochemical fields in Drake Passage using in situ observations and an eddy‐resolving numerical model. Both observations and model show a negative correlation between temperature and partial pressure of CO2 (pCO2) anomalies at the sea surface in austral summer, indicating that warm/cold anticyclonic/cyclonic eddies take up more/less CO2. In austral winter, in contrast, relationships are reversed: warm/cold anticyclonic/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 62 publications
(101 reference statements)
0
42
3
Order By: Relevance
“…As regards the magnitude of the response on air-sea carbon fluxes, however, we find that differences between contemporary approaches to define the thickness diffusivity of Gent and McWilliams (1990) are small. Our results are apparently at odds with simulations from Swart et al (2014) who consider a more limited area. This may, or may not, be related to their choice of regional averaging or differences in their biogeochemical modules: Swart et al (2014) do not resolve iron limitation explicitly and feature a retarded formulation of light limitation (Schmittner et al, 2009).…”
Section: Discussioncontrasting
confidence: 96%
“…As regards the magnitude of the response on air-sea carbon fluxes, however, we find that differences between contemporary approaches to define the thickness diffusivity of Gent and McWilliams (1990) are small. Our results are apparently at odds with simulations from Swart et al (2014) who consider a more limited area. This may, or may not, be related to their choice of regional averaging or differences in their biogeochemical modules: Swart et al (2014) do not resolve iron limitation explicitly and feature a retarded formulation of light limitation (Schmittner et al, 2009).…”
Section: Discussioncontrasting
confidence: 96%
“…This may be why pCO 2 ‐nonT has a smaller seasonal amplitude in the Southern Ocean SPSS biome than in northern SPSS biomes (Figure d). As in the northern SPSS, MLDs are positively correlated with pCO 2 (Figure d), with the scattered negative correlations at 1 × 1° (Figure c) potentially attributable to mesoscale activity [ Song et al ., ]. Chlorophyll and pCO 2 are strongly negatively correlated, due to pCO 2 ‐nonT (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The Southern Ocean is to first-order light limited and is also a high-nutrient, low-chlorophyll (HNLC) region where iron availability limits productivity [Song et al, 2016;Gervais et al, 2002;Falkowski et al, 1998]. This may be why pCO 2 -nonT has a smaller seasonal amplitude in the Southern Ocean SPSS biome than in northern SPSS biomes ( Figure 4d).…”
Section: Subpolar (Spss)mentioning
confidence: 99%
“…Second, although we showed that GM's parameterization is, in terms of the carbon uptake in the Southern Ocean, rather robust -still -all of our coarseresolution simulations could be biased. To this end, the increase in computer power is about to provide some guidance now that recent configurations can afford to resolve much of the mesoscale (e.g., Dufour et al, 2015;Bishop et al, 2016) in the Southern Ocean, and are starting to include biogeochemical and/or modules that comprise carbon (Song et al, 2016). Hence a comparison of the sensitivity of carbon uptake to increasing winds between coarse-resolution models (like the configurations tested here) and configurations that explicitly resolve mesoscale processes, is to come.…”
Section: Discussionmentioning
confidence: 99%